2022
DOI: 10.3390/antibiotics11050682
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Trends in Antimicrobial Use and Their Determinants Based on Dispensing Information Collected from Pharmacies throughout Japan: A First Report

Abstract: The purpose of this study was to evaluate the defined daily doses (DDD)/1000 prescriptions/month (DPM) as a new indicator that can be used in pharmacies, and to describe antimicrobial use patterns in pharmacies nationwide in Japan. Dispensing volumes, number of prescriptions received, and facility information were obtained from 2638 pharmacies that participated in a survey. DPM was calculated based on the dispensing volume and number of prescriptions, which are routinely collected data that are simple to use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, the use of narrow-spectrum antimicrobials is low, and that of broad-spectrum antimicrobials is still high. Muraki et al reported similar data from a nationwide investigation [12]. Since the focus is on the number of antimicrobial prescriptions and the amount of antimicrobial use, it will be necessary to monitor whether the average recovery cycle of patients lengthens in the future while antimicrobial prescriptions decrease, specifically with regard to the percentage of patients who have become severely ill. Antimicrobial prescriptions should be reduced, the patients who need antimicrobials should be prescribed them, and the choice of antimicrobials should be appropriate.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, the use of narrow-spectrum antimicrobials is low, and that of broad-spectrum antimicrobials is still high. Muraki et al reported similar data from a nationwide investigation [12]. Since the focus is on the number of antimicrobial prescriptions and the amount of antimicrobial use, it will be necessary to monitor whether the average recovery cycle of patients lengthens in the future while antimicrobial prescriptions decrease, specifically with regard to the percentage of patients who have become severely ill. Antimicrobial prescriptions should be reduced, the patients who need antimicrobials should be prescribed them, and the choice of antimicrobials should be appropriate.…”
Section: Discussionmentioning
confidence: 88%
“…This study can serve as a guideline for understanding the efficiency of the AMR Action Plan, thereby facilitating the improved implementation of the plan in Japanese community pharmacies, and promoting more suitable infection control measures and prescription practices. A nationwide study of antimicrobial prescriptions in pharmacies between 2019 and 2021 reported that the use of third-generation cephalosporins, quinolones, and macrolides in pharmacies that received prescriptions primarily from hospitals or clinics decreased [ 12 ]. However, the previous report did not cover the AMR Action Plan or the impact of the addition of the pediatric antimicrobial regimen on the appropriate use of antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 , 4 , 7–10 In Japan, the Ministry of Health, Labour and Welfare (MHLW) launched the National Action Plan (NAP) on AMR (2016–20), published the Manual of Antimicrobial Stewardship in 2017, which was mainly targeted at primary care, 11 and introduced financial incentives for appropriate outpatient AMU for paediatric patients in 2018 and for otorhinolaryngological patients in 2022. 12 , 13 Although NAP-based national interventions have reduced oral AMU to some extent, 14 their impact on AMR has not yet been assessed. National intervention through financial incentives to reduce AMU in primary care has been attempted in several countries, such as Denmark, Sweden and the UK, 15–18 but the impact of these interventions on AMR at the national level has been longitudinally assessed only in the UK.…”
Section: Introductionmentioning
confidence: 99%